Economic impacts of metaphylaxis use in U.S. feedlots: producer decisions, policy, and insurance - Dennis, Elliott J. (Kansas State University, 2019)
Net return losses due to cattle mortality and morbidity associated with bovine respiratory disease (BRD) has a substantial impact on the feedlot industry. Metaphylaxis is a common feedlot cattle health management practice used to limit cattle morbidity and mortality attributed to BRD. Efficacy of antimicrobials used for metaphylaxis is known to vary by cattle population. How this differing antimicrobial efficacy translates to net return profitability for heterogeneous cattle populations is less understood. The objective of this article is to measure the net return profitability and uncertainty of Upper Tier and Lower Tier antimicrobials used for metaphylaxis. Using information from 10 feedlots representing a half-million animals and 1500 cohorts between 1989-2015 we find the expected value of administering an Upper Tier (Lower Tier) metaphylaxis treatment compared to no treatment for high health risk steers is $90.46/head ($28.06) for 600 lb. and $118.85/head ($41.74) for 800 lb. winter placements. Furthermore, the probability or risk of net return losses worsening by at least $50/head is significantly reduced (from approximately 15 % to 4 %) when any metaphylaxis antimicrobial is used on high health risk cattle. The expected value and net return risk mitigated by metaphylaxis use on high health risk cattle varies by placement weight, season, and antimicrobial used. Although several studies have estimated economic impacts of antimicrobials for growth promotion, little is known about economic impacts of the common animal health management strategy known as metaphylaxis: administering antimicrobials to groups of animals to prevent disease. This article develops a new framework to map animal disease to producer profitability and determine societal economic impacts surrounding metaphylactic use of antimicrobials in beef cattle production. Results indicate the direct net return value of metaphylaxis to the U.S. fed cattle industry is at least $532 million. Beef producer surplus losses of $1.8 billion would be associated with eliminating metaphylaxis. Antimicrobial resistance in humans is increasing and there is growing concern that antimicrobials used in livestock production is contributing to this growth. Metaphylaxis, administering FDA approved injectable antimicrobials to high health risk livestock upon arrival at feeding operations, is one animal health strategy producers use to reduce the size or magnitude of livestock morbidity and mortality. International organizations have explicitly aimed to remove metaphylaxis for disease prevention but there is concern that few, if any, alternative health management strategies exist. Likewise, little is known about under what conditions livestock producers use metaphylaxis and if they would be willing to substitute away if a feasible market alternative were available. This article develops a theoretical framework for why metaphylaxis is used in US cattle feedlots. Our results indicate that when no market insurance is available, feedlots use more income for disease prevention than disease treatment. However, producers equalize disease treatment and prevention expenditures when an actuarially fair market insurance is available. We develop a simple elementary market insurance product that could be used and show that feedlots can improve their wealth position over metaphylaxis when a market insurance product is used.
Keywords: Animal health; Cattle; Economics; Feedlot; Insurance; Metaphylaxis